Disparitas Pembangunan Ekonomi Indonesia - Ratna Christianingrum (Pusat Kajian Anggaran, 2021)
This study aims to examine the pattern and economic structure of provinces in Indonesia using the Klassen typology. This study also aims to describe the level of inequality in provinces in Indonesia using the Williamson Index. This study used GDPR from all provinces in Indonesia in 2018-2020. This study shows that most provinces in Indonesia are classified as high-income and low-growth. During the pandemic, there were several provinces that were classified as low-income and low-growth provinces. The tertiary sector is support the economy in these provinces. This is due to changes in consumption patterns and a decrease in purchasing power during the pandemic. The concentration of regional economic activity and investment is the cause of high inequality in Indonesia.